4 × 4 matrix keyboard interface circuit achieved by single port lines. Issue 10 (1st May 2016) - Lin, Zhiqi; Shi, Xinrong
Abstract : It is usual that eight pins is used to connect the single‐chip with 4 × 4 matrix keyboard by the method of scanning. A method without any other active element is raised. Only one pin, four capacitors and four resistances are used to connect the single‐chip with 4 × 4 matrix keyboard without any other chip and active element.